The Mitochondrial Permeability Transition Pore-Current Knowledge of Its Structure, Function, and Regulation, and Optimized Methods for Evaluating Its Functional State - Endlicher, René; Drahota, Zdeněk; Štefková, Kateřina; Červinková, Zuzana; Kučera, Otto (Cells, 2023)
The mitochondrial permeability transition pore (MPTP) is a calcium-dependent, ion non-selective membrane pore with a wide range of functions. Although the MPTP has been studied for more than 50 years, its molecular structure remains unclear. Short-term (reversible) opening of the MPTP protects cells from oxidative damage and enables the efflux of Ca2+ ions from the mitochondrial matrix and cell signaling. However, long-term (irreversible) opening induces processes leading to cell death. Ca2+ ions, reactive oxygen species, and changes in mitochondrial membrane potential regulate pore opening. The sensitivity of the pore to Ca2+ ions changes as an organism ages, and MPTP opening plays a key role in the pathogenesis of many diseases. Most studies of the MPTP have focused on elucidating its molecular structure. However, understanding the mechanisms that will inhibit the MPTP may improve the treatment of diseases associated with its opening. To evaluate the functional state of the MPTP and its inhibitors, it is therefore necessary to use appropriate methods that provide reproducible results across laboratories. This review summarizes our current knowledge of the function and regulation of the MPTP. The latter part of the review introduces two optimized methods for evaluating the functional state of the pore under standardized conditions.
Keywords: Mitochondria; Calcium; transportní proteiny mitochondriální membrány; mitochondrial permeability transition pore; vápník; Mitochondrial Permeability Transition Pore; buněčná smrt; calcium signaling; calcium-induced swelling; Mitochondrial Membrane Transport Proteins; mitochondria; mitochondrial permeability transition; mitochondrie; Cell Death; přechodový pór mitochondriální permeability; calcium retention capacity